Palladium-catalyzed [3+2] annulation of allenyl carbinol acetates with C, N-cyclic azomethine imines. Issue 85 (9th October 2019) - Mao, Biming; Zhang, Junya; Xu, Yi; Yan, Zhengyang; Wang, Wei; Wu, Yongjun; Sun, Changqing; Zheng, Bing; Guo, Hongchao
Abstract : Palladium-catalyzed [3+2] annulation of allenic esters with azomethine imines affording biologically interesting tetrahydropyrazoloisoquinoline derivatives. Abstract : In this paper, a palladium-catalyzed [3+2] annulation of allenyl carbinol acetates with azomethine imines has successfully been developed under mild reaction conditions, affording biologically interesting tetrahydropyrazoloisoquinoline derivatives in high to excellent yields and with excellent stereoselectivity. The reaction follows a tandem [3+2] cycloaddition/allylation/elimination of AcOH pathway. Allenyl carbinol acetates also reacted well with in situ generated azomethine imine under cocatalysis of Ag(i )/Pd(0) catalysts in a similar reaction pathway.